ROAD MAINTENANCE MANAGEMENT STUDY BASED ON THE CORRELATION BETWEEN DAMAGE VALUES AND ROAD ROUGHNESS VALUES USING ROADLAB-PRO: KAJIAN MANAJEMEN PEMELIHARAAN JALAN BERDASARKAN KORELASI NILAI KERUSAKAN TERHADAP NILAI ROUGHNESS JALAN BERBASIS ROADLAB-PRO - Yulandi, Wiki; Elsa Eka Putri; Purnawan (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Road maintenance is important to maintain the safety and comfort of road users. Surveys are needed to determine the condition of cross-country roads. Road maintenance management along with budget costs based on the results of the correlation between the IRI method values (International Roughness Index) Software-based Roadlab Pro against the value of road surface damage by the PCI method (Pavement Condition Index) and Bina Marga can be done for the purpose of simplifying the survey process in evaluating road conditions and how to properly handle damage to the Pondok-Pulau Sangkar road section in Kerinci Regency. IRI value based on Roadlab Pro can be used to assess road conditions based on the PCI method because it has values that influence each other based on the results of correlation regression analysis with a coefficient value of 88.7%. Determination of the road maintenance budget is made based on 3 proposed scenarios which include maintenance according to needs or when damage occurs, maintenance every year, and periodic maintenance in the form of improvements in the first year, routine maintenance in the second year, and periodic maintenance from the third to the fifth year.